Expandable Ranitidine HCl tablets with Salak Bali seed matrix (Salacca zalacca) - Putra, I Gusti Ngurah Agung Dewantara; Darmaputra, I Gusti Nyoman; Tamim, Imron Hadi (International Journal Labs, 2024)
This research aims to develop ranitidine HCl tablets that can be expanded with a matrix from Balinese salak seeds (Salacca zalacca) as a natural matrix material. This formulation is expected to prolong the release time of the drug in the body, thereby increasing the effectiveness of ranitidine therapy in the treatment of gastric diseases. The research method included the extraction of the active components from Balinese salak seeds and the process of making tablets using the wet granulation method, followed by physical tests of the tablets which included the hardness, crushing time, and ability of the tablets to expand. The results showed that ranitidine HCl tablets with Balinese salak seed matrix had physical characteristics that met the requirements of pharmacopooeia, with a slower drug release time than tablets without a developer matrix. Analysis of development capabilities shows that Balinese salak seeds are effective as natural matrix agents to prolong the release time of ranitidine HCl. In conclusion, Balinese salak seed matrix can be used as an alternative in the development of expandable ranitidine HCl tablets, potentially increasing the therapeutic effect of the drug.